2014
DOI: 10.1097/mbc.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Congenital afibrinogenemia in a new born

Abstract: Bleeding in the neonates may be a result of thrombocytopenia, sepsis or vitamin K deficiency. Congenital bleeding disorders are a rare cause of bleeding. The umbilical cord bleed is an important clue to underlying bleeding disorders especially factor XIII deficiency and afibrinogenemia. In some laboratories, the routine workup for the bleeding neonate may not always include fibrinogen assays, which may then delay this diagnosis. We report a case of congenital afibrinogenemia in a neonate who presented with umb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Consistent with the above findings, we found that only 38.8% of neonates showed hemorrhage, which mostly presented as the mild form in approximately 60.9% of the cases. Similar to previous studies, hemorrhage in neonates manifested as puncture site bleeding, spontaneous skin/mucous membrane bleeding, and umbilical cord bleeding ( 9 , 15 , 17 , 22 , 23 , 26 ). Nonetheless, hypofibrinogenemia can also present with potentially life-threatening hemorrhage such as intracranial bleeding ( 10 , 14 , 16 , 19 , 20 ), which was also detected in a small number of infants in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with the above findings, we found that only 38.8% of neonates showed hemorrhage, which mostly presented as the mild form in approximately 60.9% of the cases. Similar to previous studies, hemorrhage in neonates manifested as puncture site bleeding, spontaneous skin/mucous membrane bleeding, and umbilical cord bleeding ( 9 , 15 , 17 , 22 , 23 , 26 ). Nonetheless, hypofibrinogenemia can also present with potentially life-threatening hemorrhage such as intracranial bleeding ( 10 , 14 , 16 , 19 , 20 ), which was also detected in a small number of infants in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Although the incidence of hemorrhage was not associated with FIB, as reported previously (17), the incidence of bleeding events was significantly associated with the presence of other coagulation abnormalities. Moreover, the incidence of hemorrhage was not significantly different when hypofibrinogenemia occurred alone or in combination with thrombocytopenia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The coagulation disorders of brinogen include congenital disorders of brinogen disease and acquired disorders of brinogen disease. The congenital disorders of brinogen includes a brinogenemia, hypo brinogenemia, dys brinogenemia [1,2], the rst two of which are quantity of brinogen abnormality (a brinogenemia is de ned as brinogen in plasma less than 50mg/dl, hypo brinogenemia is de ned as brinogen in plasma from 50mg/dl to 150mg/dl [3]), the last of which are brinogen activity decreased (dys brinogenemia) [1,2]. Congenital hypo brinogenemia is autosomal recessive hereditary disease [4], which was rst reported in 1953 [5]and in the population, the morbidity rate is 1/1000000 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of this disease can be asymptomatic, bleeding, and rare thrombosis [3,7]. The main treatment for congenital hypo brinogenemia is brinogen replacement therapy(fresh frozen plasma, cryoprecipitate or brinogen concentrate) [2]. Fibrinogen, a 340Kd glycoprotein produced by liver, is the main substance in the process of coagulation and thrombosis [8].…”
Section: Introductionmentioning
confidence: 99%